Hypermethylation of CpG islands and shores around specific microRNAs and mirtrons is associated with the phenotype and presence of bladder cancer. - Dudziec, E; Miah, S; Choudhry, H; Owen, H; Blizard, S; Glover, M; Hamdy, F; Catto, J (2011)
PURPOSE: To analyze the role and translational potential for hypermethylation of CpG islands and shores in the regulation of small RNAs within urothelial cell carcinoma (UCC). To examine microRNAs (miR) and mirtrons, a new class of RNA located within gene introns and processed in a Drosha-independent manner. EXPERIMENTAL DESIGN: The methylation status of 865 small RNAs was evaluated in normal and malignant cell lines by using 5-azacytidine and microarrays. Bisulfite sequencing was used for CpG regions around selected RNAs. Prognostic and diagnostic associations for epigenetically regulated RNAs were examined by using material from 359 patients, including 216 tumors and 121 urinary samples (68 cases and 53 controls). Functional analyses examined the effect of silencing susceptible RNAs in normal urothelial cells. RESULTS: Exonic/UTR-located miRs and mirtons are most susceptible to epigenetic regulation. We identified 4 mirtrons and 16 miRs with CpG hypermethylation across 35 regions in normal and malignant urothelium. For several miRs, hypermethylation was more frequent and dense in CpG shores than islands (e.g., miRs-9/149/210/212/328/503/1224/1227/1229), and was associated with tumor grade, stage, and prognosis (e.g., miR-1224 multivariate analysis OR = 2.5; 95% CI, 1.3-5.0; P = 0.006). The urinary expression of epigenetically silenced RNAs (miRs-152/328/1224) was associated with the presence of UCC (concordance index, 0.86; 95% CI, 0.80-0.93; ANOVA P < 0.016). CONCLUSIONS: Hypermethylation of mirtrons and miRs is common in UCC. Mirtrons appear particularly susceptible to epigenetic regulation. Aberrant hypermethylation of small RNAs is associated with the presence and behavior of UCC, suggesting potential roles as diagnostic and prognostic biomarkers.